Religious Authority Between Lineage and Merit: An Ethnographic Study of Habaib’s Identity Negotiation in Pesantren - Irama, Yoga; Al Amin, Ainur Rofiq (Journal of Islamic Thought and Philosophy, 2025)
This study analyzes the process of negotiating the identity and religious authority of the habaib at the Pesantren Sholahuddin in Surabaya. Historically viewed as descendants of the Prophet, the habaib are no longer accepted unconditionally but are continually negotiated based on their knowledge, morals, and social roles. Using a qualitative approach and ethnographic methods—including participatory observation, in-depth interviews, and documentation—the study found that Pesantren Sholahuddin does not rely solely on lineage but also emphasizes scholarly credentials, lineage, and moral integrity. In this negotiation process, there is a dynamic construction of identity and authority, where lineage, scholarly knowledge, and moral character complement and compete with one another. This research makes an important contribution to the study of religious authority and the role of pesantren institutions as spaces for identity negotiation. It also demonstrates that religious leadership in Indonesia is not a monolithic entity but is formed through processes of negotiation and contestation based on multidimensional criteria.